Fadiga em compósitos 5HS carbono/epóxi processados via RTM: relação entre cargas axiais no plano e modos de delaminação - Shiino, Marcos Yutaka [UNESP] (2015)
Carbon fiber composite materials are currently widely employed in air transportation as structural components in Boeing 787 Dreamliner, which has around 80% (v/v) in composite. However these materials are susceptible to delamination due to low strength in through-the-thickness direction which is the driving force to reduce the fatigue life. Considering the importance of delamination, the aim of this research is to have a clear understanding of this type of damage in woven composites by using the Griffith energy approach of the linear elastic fracture mechanics as a delamination parameter. The aim of this work was to achieve insight into the interaction process of crack propagation modes I and II, and mainly to determine the mode fractions in the delamination process of tension-tension axial fatigue tests. For the mode decomposition process from axial fatigue tests, it was employed two failure criteria. In order to obtain it, the crack growth rate associated with pure modes I and II delamination were compared with the behavior of a specimen subjected to in-plane tension-tension cyclic loading that exhibits a mixed delamination mode for which needed an appropriate specimen geometry to generate a sharp delamination front. Fatigue test in all modes of propagation were conducted with a loading ratio of 0,1 and a frequency of 5 Hz. The crack growth rate versus energy release rate was described by an appropriate empirical power law which fits the experimental results and compared with delamination mechanisms observed by fractography. The results showed that the driving force for fatigue has major influence of GIc and Gmax based on the studied fractures, where both were considered in the Paris law. For the mixed mode, the geometry known as CLS had regions of crack propagation rate comparable to pure delamination modes in the stable propagation region which ... (Complete abstract click electronic access below)